Design and Implementation of Continuous Settling Tank (CST) Temperature Monitoring System and Waste Pond Level in a Palm Oil Mills - Ulhaq, Muhammad Dafa; Ullah, Aulia; Mansyurdin, Muharpi; Zarory, Hilman; Faizal, Ahmad (Jurnal Sistem Cerdas, 2024)
Improving time efficiency and reducing work risks are crucial in palm oil mill operations. Two vital factors in palm oil mill operations are CST temperature and effluent pond level. Both of these factors have a significant impact on mill efficiency. Extreme temperatures, either too high or too low, can disrupt the settling and separation process of water, oil and sludge. In addition, overflowing effluent pond levels are often missed by technicians, so checking must be done manually. This research aims to develop a monitoring system that can monitor the temperature of the CST in safe conditions and measure the level of the waste pond in real-time by utilizing Internet of Things (IoT) technology. This control system relies on components such as the NodeMCU ESP8266 microcontroller, DS18B20 temperature sensor, and HC-SR04 proximity sensor. The method used is the design and manufacture of a prototype monitoring system. Field test results show that this system is able to make comparisons with manual measurement methods. In testing the CST temperature sensor and the waste pool level sensor, the accuracy rate reached 100%. The temperature was successfully monitored with a safe limit of 89°C, while the waste pool level was monitored through the monitoring website. This Internet of Things-based monitoring system has shown significant potential in improving the efficiency and safety of palm oil mill operations, and enables mill operators to effectively conduct remote real-time monitoring.